THE INFLUENCE OF FINANCIAL PLAN SUPPORT, LUCIDITY OF FINANCIAL PLAN OBJECTIVES, FINANCIAL PLAN ACKNOWLEDGMENT AND HIERARCHICAL RESPONSIBILITY AS A MODERATING VARIABLE IN THE ORGANIZATION OF REGIONAL APPARATUS OF NORTH SUMATRA PROVINCE - Zaki Baginda Muhammad Amin; Irfan; Maya Sari (Jurnal Ekonomi, 2023)
The research objective is to analyze the effect of organizational commitment on moderating budgetary participation on budget realization, and also to analyze the effect of organizational commitment on moderating the clarity of budget objectives on budget realization. The approach used in this research is a quantitative associative approach. Data was collected using a questionnaire. The sample in this study was 38 ProvSu Regional Apparatus Operations (OPD), each OPD representing 4 fields of 152 samples. Data were analyzed using SEM-PLS. the consequences of the review expressed that there was an impact of financial plan interest on spending plan acknowledgment, there was an impact of authoritative responsibility on directing spending plan investment on financial plan acknowledgment, there was an impact of hierarchical responsibility on directing the lucidity of financial plan focuses on financial plan acknowledgment.